Esophagojejunostomy using a circular stapler vs. a linear stapler for gastric cardia cancer patients: impact of upper margin length and tumor size on the survival rate - Dieudonne, Maniragaba; Lv, Renguang; Xie, Wenjie; Liu, Qi; Jiang, Jianwu; Fu, Yang (Frontiers in Surgery, 2024)
BackgroundThe incidence of gastric cancer is concomitantly rising with gastric cardia cancer worldwide. While the improvement of gastric cancer surgical techniques is glowing, this study assesses the impact of the upper margin length and tumor size on the survival rate for gastric cardia cancer patients who underwent total laparoscopic total gastrectomy(TLTG) or laparoscopic assisted total gastrectomy(LATG).Materials and methodsA total of 63 patients with gastric cardia cancer who underwent laparoscopic total gastrectomy were retro-prospectively collected from January 2021 to May 2023. While assessing the impact of upper margin length and tumor size on the survival rate, esophagojejunostomy using a linear stapler has been compared to a circular stapler.ResultsThe sixty-three patients met inclusion criteria; 32 (51%) underwent LATG and 31 (49%) underwent TLTG. Their mean age was 65 years (range, 45–77). The blood loss means in LATG and TLTG was 74.69 and 50.16 ml, respectively (p = 0.005), and surgery duration was higher in LATG than LATG with respective means of 247 min and 222.42 min. (p = 0.006). However, the tumor size means (p = 0.5), and upper margin length means (p = 0.052) were not significantly different in the LATG and TLTG groups, respectively. The number of resected and assessed lymph node was adequate in the LATG and TLTG groups. The current study still does not find an independent related risk from the upper margin length and tumor size to the survival rate according to the multiple regression analysis (p = 0.080).ConclusionThe upper margin length and tumor size do not have a relationship with the survival rate of the compared esophagojejunostomy (EJS) methods. The EJS using a linear stapler requires a shorter surgery duration and less blood loss than EJS using a circular stapler.